Calidad de la canal de bovinos enteros F1 Aberdeen Angus x Brahman y Brangus en Colombia (2015)
ABSTRACT: The internationalization of markets and the requirements of these have encouraged the use of crossbreeding in beef cattle production in our country. The Angus breed is well known for its production, efficiency and quality of the final product while Brahman is recognized for its ability to produce beef in tropical conditions due to its adaptation. The crossbreeding between them in different proportions is gaining importance each and every day. The aim of this study was to perform a comparative analysis of some carcass quality characteristics of F1 Aberdeen Angus x Brahman bulls compared to Brangus bulls (5/8 Aberdeen Angus 3/8 Brahman) sold in Medellin city. It was evaluated the carcass of 45 bulls based on the following variables: age, carcass length (CL), leg circumference (PP), degree of ossification (OC1, OC2 and OC3), fat (G1 and G2), the weight of the hot carcass (PCC), weight of the cold carcass (PCF) and total usable beef (TCA), using the parameters determined by the Institute of classification of Food Science and Technology - National University ICTA,Colombia.The carcasses of F1 A x B bulls had higher cold carcass weight, more beef, thicker backfat and greater degree of ossification as an indicator of physiological maturity compared with the carcasses of Brangus bulls (5/8 A 3/8 B). No significant differences were found in other variables. This research demonstrates the advantages conferred by hybrid vigor in F1 cattle under the conditions tested.